2013
DOI: 10.1016/j.jmb.2013.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origins of Cofilin-Linked Changes in Actin Filament Mechanics

Abstract: The actin regulatory protein cofilin plays a central role in actin assembly dynamics by severing filaments and increasing the concentration of ends from which subunits add and dissociate. Cofilin binding modifies the average structure and mechanical properties of actin filaments, thereby promoting fragmentation of partially decorated filaments at boundaries of bare and cofilin-decorated segments. Despite extensive evidence for cofilin-dependent changes in filament structure and mechanics, it is unclear how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 64 publications
9
54
0
Order By: Relevance
“…These observations suggest that stiffness cation occupancy is coupled to the D-loop conformation and radial distribution of long-axis contacts between adjacent filament subunits ( Fig. 1 D, E, G, and H), consistent with a role for the D-loop conformation in controlling filament mechanical properties (10,(24)(25)(26).…”
Section: Significancesupporting
confidence: 66%
See 2 more Smart Citations
“…These observations suggest that stiffness cation occupancy is coupled to the D-loop conformation and radial distribution of long-axis contacts between adjacent filament subunits ( Fig. 1 D, E, G, and H), consistent with a role for the D-loop conformation in controlling filament mechanical properties (10,(24)(25)(26).…”
Section: Significancesupporting
confidence: 66%
“…Several observations argue against this interpretation. Salts and electrolytes weaken ionic bridges between charged protein residues (36, 37), which would compromise intersubunit contacts and lower the filament stiffness (10,38). In contrast, Mg 2+ enhances intersubunit contacts (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…One of the remarkable and unusual properties of actin filaments is that cofilin bindings alter the helical structure of the filaments (26-28); they are more compliant in bending (29)(30)(31) and twisting (12,32). Because our recent study suggested that cofilin prefers to bind actin filaments with less tension and that actin filaments with less tension showed larger torsional fluctuations (33), we expected that the on-rate of cofilin bindings would be larger at more fluctuating regions of the actin filament.…”
Section: Positive Correlation Between Cofilin Binding and Fluctuationmentioning
confidence: 99%
“…The analysis of torsional fluctuations in actin filaments (12,32,37) showed that the amplitude of spontaneous fluctuations would twist actin filaments to a degree comparable with the twist when filaments are decorated with cofilin (4). These results suggest that spontaneous structural fluctuations of actin filaments enable cofilin binding to the filaments.…”
Section: Biophysical Mechanism Of Cooperative Cofilin Binding To Actimentioning
confidence: 99%